Clinical bioethics in the face of technological innovation: challenges in the treatment of terminal illnesses - Mancera-Guzmán, Claudia Liliana (2025)
In the current era, technological innovation has profoundly transformed diagnostic and treatment methods in medicine, including the treatment of terminal illnesses. However, this revolution has also generated significant ethical challenges, especially in the field of clinical bioethics. This article analyzes the bioethical dilemmas that arise with the use of innovative technologies in the treatment of terminal illnesses, with an emphasis on autonomy, human dignity, and therapeutic proportionality. Through in-depth analysis, it explores the implications of technologies such as artificial intelligence, telemedicine, and remote monitoring devices. In addition, it examines the new frontiers of palliative care, highlighting how these innovations can improve quality of life or, in some cases, complicate the process of dying with dignity.